(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The study sought to determine effect of female career development on performance Money Deposit Banks, identify the obstacles of female career development in money deposit banks. The study had a population size of 3152, out of which a sample size of 354 was realised using taro Yamanes formula at 5% error tolerance and 95% level of confidence. Instrument used for data collection was primarily questionnaire and interview. Out of 354 copies of the questionnaire that were distributed, 334 copies were returned while 47 were not returned. The survey research design was adopted for the study. The hypotheses were tested using Pearson chi-square and simple linear regression statistical tools. The findings indicated that Female career development significantly affects performance of money deposit banks (r = 0.766; t =13.191; F= 52.361; p < 0.05) . Glass ceiling, Gender inequality and cultural factor are the obstacles of female career development in money deposit banks (X2c =136.379, > X2t =31.419; p,< .05).The study concluded that women world-wide can be seen joining the workforce in large numbers. Women managers globally are described as having to deal with blocked mobility, discrimination and stereotypes. The study recommended that The equality theory should be adopted in any money deposit banks, and gender issues should be a thing of the past, but employee input should determine their reward system and promotion. In order increase productivity government should empower women and protect their labour rights and the environment through the policies put in place.